Democratic regressions in Asia - Croissant, Aurel; Haynes, Jeffrey (London, 2023)
The book studies and compares causes, catalysts and consequences of democratic regression and revival in South, Southeast, and Northeast Asia. - The Asia-Pacific presents social scientists with a natural laboratory to test competing theories of democratic erosion, decay, and revival and to identify new patterns and relationships. This volume combines conceptual and comparative research with single case studies. Overall, the collection of studies in this volume captures different forms of democrati
Keywords: Aufsatzsammlung; Demokratieforschung; Ostasien